Visual Encoding of Acoustic Parameters - Framework and Application to Noise Mapping. (1st November 2013) - Schiewe, Jochen; Weninger, Beate
<x xml:space="preserve">Abstract</x> Along with an increasing importance and awareness of sonic phenomena related to the human environment, there is a growing need for a comprehensive communication of sound information. The central goal of this contribution is the development of a systematic and comprehensive framework that considers the particular properties of sound phenomena. This framework is structured according to the acoustic quantities that shall be represented and consists of recommendations for their cartographical encoding. A proof of concept is given through the application to official strategic noise maps in the course of the Environmental Noise Directive. Those maps suffer from several weaknesses from a cartographical point of view (e.g. concerning colour schemes or band-like illustrations) which can be eliminated by applying some of the mentioned recommendations. Finally, it will be possible to derive valuable knowledge from our results for multimodal encoding and value transformation between senses.